A selected small molecule prevents inflammatory osteolysis through restraining osteoclastogenesis by modulating PTEN activity. Issue 8 (1st December 2020) - Chen, Yueqi; Hu, Wenhui; Wang, Yiran; Li, Yuheng; Li, Xiaoming; Li, Haibo; Tang, Yong; Zhang, Lincheng; Dong, Yutong; Yang, Xiaochao; Wei, Ye; Dong, Shiwu
Abstract: Background: Inflammatory osteolysis is a severe infectious bone disorder that occurs during orthopaedic surgery and is caused by disruptions in the dynamic balance of bone matrix homeostasis, which makes this condition a burden on surgical procedures. Developing novel therapeutic drugs about inhibiting excessive osteoclastogenesis acts as an efficient approach to preventing inflammatory bone destruction. Methods: To study this, we explored the potential effects and mechanisms of compound 17 on inflammatory osteolysis in vitro. Meanwhile, a lipopolysaccharide (LPS)‐induced calvarial osteolysis mouse model was used to evaluate the protective effect of compound 17 on inflammatory bone destruction in vivo. Results: In our study, we found that compound 17 could inhibit osteoclast (OC) differentiation and bone resorption during RANKL and LPS stimulation in a time‐ and dose‐dependent manner, while compounds 5 and 13 did not have the same effects. Mechanistically, compound 17 promoted phosphatase and tensin homologue (PTEN) activity by reducing PTEN ubiquitination, thereby restraining the RANKL‐induced NF‐κB pathway, resulting in the inhibition of the expression of osteoclastogenesis‐related genes and the formation of the NLRP3 inflammasome. Additionally, we also investigated whether compound 17 could negatively modulate macrophage polarization and repolarization due to its anti‐inflammatory effects. Moreover, compound 17 also plays an important role in osteoblast differentiation and mineralization. In vivo experiments showed that compound 17 could effectively protect mice from LPS‐induced inflammatory bone destruction by inhibiting osteoclastogenesis and inflammation. Conclusions: Taken together, these results show that compound 17 might play protective role in inflammatory bone destruction through inhibiting osteoclastogenesis and inflammation. These findings imply a possible role of compound 17 in inflammatory osteolysis‐related diseases. Abstract : A selected compound 17 small molecule suppressed osteoclastogenesis in vitro by inducing PTEN activity by restraining PTEN ubiquitination, thus inhibiting the RANKL‐induced NF‐κB pathway. The polarization and repolarization of M1 macrophages were also negatively modulated. In vivo experiments showed that compound 17 prevented LPS‐induced inflammatory osteolysis by inhibiting OC activity. All in all, compound 17 might act as a potential novel drug to treat inflammatory osteolysis‐related diseases in the future.